Trading Frictions and Futures Price Movements - Goldenberg, David H. (Journal of Financial and Quantitative Analysis, 1988)
In a perfectly efficient market, after adjusting for drift, futures prices would follow a martingale model. The martingale property implies that the changes in futures prices should be serially uncorrelated. This study finds that the price changes of the S&P 500 futures contracts during 1983 and 1984 have negative serial correlation and are better described by a random walk model with reflecting barriers or by a random walk model with reflecting barriers and mean reversion.